PENGARUH LATIHAN SCALE BAND TERHADAP KELENTURAN OTOT PUNGGUNG SAAT MELAKUKAN SMASH PADA PERMAINAN BOLA VOLLI TIM BOLA VOLLI SMK TARUNA SATRIA PEKANBARU - Tirto, Anggi; ', Ramadi; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract This study is an experiment.Using experimental and statistical analysis to examining the research done on the sampel. Obtained through an initial test and final test before and after exercise to compare the one groups of sampel with different treatments to fine that practice which is better for Flexsibelity are nice. Due to lack of physical exercise and training programs that are less systematic. The issues raised in this study is